Occurrence, distribution, and risk assessment of pharmerciuticals in wastewater and open surface drains of peri-urban areas: Case study of Juja town, Kenya. (December 2020) - Muriuki, Cecilia W.; Home, Patrick G.; Raude, James M.; Ngumba, Elijah K.; Munala, Gerryshom K.; Kairigo, Pius K.; Gachanja, Anthony N.; Tuhkanen, Tuula A.
Abstract: The occurrence of Active Pharmaceutical Ingredients (APIs) in the environment is becoming a major area of concern due to their undesirable effects on non-target organisms. This study investigated the occurrence and risk of contamination by five antibiotics and three antiretrovirals drugs in a fast-growing peri-urban area in Kenya, with inadequate sewer system coverage. Due to poor sewage connectivity and poorly designed decentralized systems, wastewater is directly released in open drains. Water and sediment samples were collected from open surface water drains, while wastewater samples were collected from centralized wastewater treatment plants (WWTP). Solid-phase extraction and ultrasonic-assisted extraction for the aqueous and sediment samples respectively were carried out and extracts analyzed by liquid chromatography-electrospray ionization tandem mass spectrometry (LC-ESI-MS/MS) using isotopically labeled internal standards. APIs were observed with the detection frequency ranging from 36% to 100%. High mean concentrations of 48.7 μg L −1, 108 μg L −1, and 532 μg L −1 were observed in surface drains for Lamivudine (3 TC), Sulfamethoxazole (SMX), Ciprofloxacin (CIP) respectively. Drain sediments also showed high concentrations of APIs ranging from 2.1 to 13, 100 μg kg −1 . APIs in this study exceeded those observed in existing literature studies. JKUAT WWTP removal efficiencies varied from −90.68% to 72.67%. Total APIs emission load of the study area was 3550 mg d −1 with WWTP effluent contributing higher loads (2620 mg d −1 ) than surface water drains (640 mg d −1 ). Zidovudine (ZDV), nevirapine (NVP), and trimethoprim (TMP) loads in drains, however, exceeded WWTP effluent. Low to high ecotoxicity risk of the individual APIs were observed to the aquatic environment, with high risks for the development of antibiotic resistance in microbiome as determined by the risk quotient (RQ) approach. Risk management through efficient wastewater collection, conveyance, and treatment is necessary to suppress the measured concentrations. Graphical abstract: Image 1 Highlights: Detection frequency of 36–100% for five antibiotics and three antiretroviral drugs. Concentrations ranging from 0.3 to 913 μgL −1 observed in peri-urban open drains. APIs emission is higher from point pollution sources than non-point sources. Poor APIs removal efficiencies ranging from −90.7% to 40.7% in stabilization ponds. High antibiotic resistance risks in open drains, treated wastewater, and river.